Changi International Airport modelling and visualization - Kumar, Vaibhav (Nanyang Technological University, 2020)
The purpose of this project was to design and fabricate a scaled model of Changi International Airport (CIA) to study the effects of taxiway design on ground conflicts. This was achieved by manipulating OpenFlight models into Solid files with the use of 3Ds Max, AutoCAD, AutoDESK Inventor, and AutoDesk Fusion 360. The models were designed to be modular to facilitate LEGO-like freedom in altering the taxiway design. Additionally, wireless cameras were mounted on top of the Air Traffic Control Tower model to simulate the Smart Tower capability that is currently installed on the actual ATC Tower of CIA. The Smart Tower system serves to lighten the load on ATC officers by employing cameras and sensors to detect and track vehicles on the ground. The system augments crucial data onto screens for ATC Officers to monitor and keep track of potential runway and taxiway incursions. The second part of this project required the projection of vivid animations onto the model to simulate ground operations. This was done by manipulating the past traffic data of CIA into animations. A projection mapping software, HeavyM, was then used to arrange several layers of graphics and animations to give a vibrant simulation of ground operations of CIA. Difficulties with the manipulation of the OpenFlight files in the course of this Final Year Project had an adverse effect on projection mapping. This was overcome through the use of Magix to 3D print the needed files. Despite the abovementioned problem, the final demonstration yielded a realistic looking models of CIA with a Smart Tower mock-up and impressive projection mapping that relayed potential points of conflict in ground operations. There is potential for future work in creating a dynamic and responsive system using the work outlined in this report as a base.